A Diagnostic Study on the Reading Competencies of Maguindanaon Students as a Basis for Designing an Interactive and Culturally Relevant Instructional Module - DUMATO, ROHANIE (International Journal of Arts, Sciences and Education, 2025)
Reading skills are an essential factor in academic learning, yet many students encounter difficulties in understanding and analyzing the texts they read, such as literal, integrative, critical, interpretative, and creative comprehension. This study was conducted to assess the reading skills of Maguindanaon Grade 8 students at Esperanza National High School, Esperanza, Sultan Kudarat, and to develop an Interactive Module as a teaching intervention. The Research and Development (R&D) design was utilized to evaluate reading skills, address identified problems, and assess the effectiveness of teachers’ and students’ acceptance of the developed teaching material. The analysis of the data showed that the reading skills of the Maguindanaon students were at a low level, particularly in literal and creative comprehension. To address this, an Interactive Module was developed. This teaching material aims to improve the reading skills of Maguindanaon students. Based on the validation results, it was found that the material had a high level of effectiveness, which means it is suitable as a teaching intervention. Furthermore, both teachers and students gave positive feedback on the Interactive Module, showcasing its potential as an effective tool for enhancing reading skills. Given the positive results of the study, the use of the Interactive Module in teaching reading is recommended to help students further develop their ability to understand and analyze the texts they read. In addition, further research is suggested to enhance and expand the application of this material in various educational contexts.